(untitled) (Orchid Academia Siraha, 2024)
This auto-ethnography study explores the life-changing experience of a marginalized Madheshi scholar in Nepal. The first author personal experiences and perspectives are examined, extending from his early years in the Terai region. The first author’s life story and the socioeconomic obstacles he faced are reflexively analyzed as core methodology, auto-ethnography through the integration of personal accounts with primary reflective data sources. His experiences provide important insights into the challenges faced by marginalized populations as they strive for acceptance and empowerment. The first author emphasized the transformative power of education in furthering social justice by arguing access to education. In conclusion, "Margins to Milestones" is for conducting academic study and engaging in introspective personal introspection in order to create a more equal and inclusive society, in addition to presenting Yadav’s life-changing journey.